Effect of Rhodococcus bioaugmentation and biostimulation on dibenzothiophene biodegradation and bacterial community interaction in petroleum-contaminated soils - Chen, Wenjie; Zuo, Yilin; Hou, Zhuonan; Wang, Bo; Xiong, Shangao; Ding, Xiaoyan; Peng, Bihui; Zhou, Kaiyun; Li, Ji; Liu, Rui; Ding, Guochun; Wei, Yuquan; et al. (Frontiers in Environmental Science, 2023)
Bioremediation can be effective method for achieving polycyclic aromatic hydrocarbons (PAHs) degradation in soil contaminated with petroleum. The aim of this study was to compare the effect of Rhodococcus bioaugmentation (BIOE) and biostimulation (BIOS) on dibenzothiophene biodegradation and bacterial community interaction in petroleum-contaminated soils. The findings revealed that compared to natural degradation treatment (NAT) and BIOS, BIOE had the highest dibenzothiophene (DBT) and the majority of DBT degradation occurred within the first 30 days. BIOS had a positive impact in the early stage but an opposite effect in the later stages for degrading DBT. Beta diversity analysis revealed significant differences of bacterial composition among NAT, BIOS, and BIOE. Sequencing results indicated that Bacillus and Paenibacillus were dominant genera involved in DBT degradation. Network analysis revealed co-occurrence patterns and connectivity, with BIOE exhibiting higher connectivity and the highest number of links in BIOS. In summary, Rhodococcus bioaugmentation was the simplest and effective method to enhance the clustering degree of bacterial network and DBT degradation in petroleum-contaminated soil, compared to NAT and BIOS.